2009
DOI: 10.1007/s00701-009-0531-y
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric colloid cysts of the third ventricle: management considerations

Abstract: Pediatric colloid cysts are rarer than their adult counterparts due to their late detection only after manifestations of raised intracranial pressure, visual or cognitive dysfunction or drop attacks occur. Their radiological appearance varies depending upon the amount of mucoid content, cholesterol, proteins, and water content. The fast development of clinical manifestations in children may be related to rapid enlargement of cyst due to higher water content within them. The transcallosal approach is the "gold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 53 publications
2
25
0
4
Order By: Relevance
“…Pediatric cases have been associated to a more aggressive clinical and radiological pattern compared to their adult counterparts [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric cases have been associated to a more aggressive clinical and radiological pattern compared to their adult counterparts [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Такие новообразования составляют 5-8% в струк-туре опухолей головного мозга, более характерны для молодого возраста [1][2][3][4][5].…”
unclassified
“…Применение современных методов нейровизуа-лизации позволило повысить качество диагностики опухолей, более четко представлять их топографо-ана-томические особенности, взаимосвязь со структурами головного мозга, что расширило возможности разра-ботки новых хирургических доступов и радикального удаления глубоко расположенных новообразований [3, [5][6][7][8][9][10][11][12][13].…”
unclassified
See 1 more Smart Citation
“…Based on previous studies, children are reported to make up 11-16% of all patients with colloid cysts [4,7]. The majority of colloid cysts diagnosed are situated in the third ventricle [8]. They also arise from several unusual locations such as the chiasma, sellar area and unilateral ventricle [9,10].…”
Section: Introductionmentioning
confidence: 99%